Natural flavonoids as antidiabetic agents. The binding of gallic and ellagic acids to glycogen phosphorylase b. Issue 15 (14th May 2015) - Kyriakis, Efthimios; Stravodimos, George A.; Kantsadi, Anastassia L.; Chatzileontiadou, Demetra S.M.; Skamnaki, Vassiliki T.; Leonidas, Demetres D.
Abstract : We present a study on the binding of gallic acid and its dimer ellagic acid to glycogen phosphorylase (GP). Ellagic acid is a potent inhibitor with K i s of 13.4 and 7.5 μM, in contrast to gallic acid which displays K i s of 1.7 and 3.9 mM for GPb and GPa, respectively. Both compounds are competitive inhibitors with respect to the substrate, glucose‐1‐phoshate, and non‐competitive to the allosteric activator, AMP. However, only ellagic acid functions with glucose in a strongly synergistic mode. The crystal structures of the GPb‐gallic acid and GPb‐ellagic acid complexes were determined at high resolution, revealing that both ligands bind to the inhibitor binding site of the enzyme and highlight the structural basis for the significant difference in their inhibitory potency. Abstract : Ellagic acid is the most potent inhibitor of natural origin that binds at the glycogen phosphorylase inhibitor site. Gallic acid is a weak inhibitor that also binds at the inhibitor site of glycogen phosphorylase. Ellagic acid's binding interacts strongly with glucose binding to GPb whereas gallic acid's does not.